2014
DOI: 10.1002/adfm.201401796
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Enhancement of Raman Scattering in Graphene‐Nanoparticle Hybrids

Abstract: The realization of graphene‐gold‐nanoparticle (G‐AuNP) hybrids is presented here through a versatile electrochemical approach, which allows the continuous tuning of the size and density of the particles obtainable on the graphene surface. Raman scattering from graphene, which is significantly enhanced in such hybrids, is systematically investigated as a function of the size and density of particles at the same location. In agreement with theory, it is shown that the Raman enhancement is tunable by varying pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 34 publications
(51 citation statements)
references
References 70 publications
(128 reference statements)
5
46
0
Order By: Relevance
“…5,21 Moreover, once the metallic nanostructures were fabricated, the plasmonic nanostructures were fixed, and their optical properties were seldom tuned. 12 Here, we show that a simple well defined system, i.e., a single gold nanorod (AuNR) and monolayer graphene hybrids, is helpful in understanding the basics of SERS. 22 And, the plasmonic resonance of the metallic nanostructures can be tuned in situ with photothermal reshaping method to investigate SERS of graphene elaborately.…”
mentioning
confidence: 98%
See 3 more Smart Citations
“…5,21 Moreover, once the metallic nanostructures were fabricated, the plasmonic nanostructures were fixed, and their optical properties were seldom tuned. 12 Here, we show that a simple well defined system, i.e., a single gold nanorod (AuNR) and monolayer graphene hybrids, is helpful in understanding the basics of SERS. 22 And, the plasmonic resonance of the metallic nanostructures can be tuned in situ with photothermal reshaping method to investigate SERS of graphene elaborately.…”
mentioning
confidence: 98%
“…[6][7][8][9] Most SERS-active systems studied to date are based on ensemble and random nanostructures. [10][11][12][13][14][15][16][17][18][19][20] For instance, different metallic nanostructures have been prepared by nanofabrication or wetchemical synthesis, and the nanostructures were deposited on graphene or were covered by graphene. Only a few reports talk about the interaction of a single plasmonic nanostructure with the graphene.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, many groups focused on in-deep understanding of the effect inspecting various scenarios. [2,13] For example, Sun et al proposed that a large SERS enhancement is a joint effect of the charge transfer and electromagnetic coupling, which is closely correlated with the near-field plasmon coupling of Ag nanoparticles in contact with the graphene bilayer. [14] He et al studied the Raman signal enhancement using Au nanorods [15] and concluded that when the resonant wavelength of the Au nanorods matches well with excitation laser wavelength, the Raman enhancement factor is highest up to 1,000-fold.…”
mentioning
confidence: 99%